Study of influence Plasma Arc cutting with response surface method - Mohd Faiz Che Dir (Universiti Malaysia Perlis, 2008)
The properties of plasma generated for the air plasma cutting process have been investigated in this study. The plasma arc cutting process employs a plasma torch with a very narrow bore to produce a transferred arc to the workpiece at an average current density of within the bore of the torch. Selco Genesis 90 Plasma Arc Cutting machine was used in this study. The first part of this study, Material Removal Rate (MRR) and Surface Roughness (Ra) can been measured in a wide range of cutting parameters. The cutting parameter is current flow rate [A],air pressure [Bar],cutting speed [mm/min] and arc gap [mm] for oxygen plasma arc cutting of Nickel-Bass Alloy. In the second part of the study, models by which to measured maximize MRR and minimize Ra are presented the best combination using Design Expert by Response Surface Method. Comparison of calculated and measured values of maximum and minimum allowed us to obtain the efficiency with which the arc power is consumed by the cutting process. It is shown that the efficiency rises as the cutting speed significant. Confirmation test have done to confirm the value estimated through the software. The confirmation for MRR run was done by using the setting of 6.0 bar (air pressure), 60 A (current flow rate), 1000 mm/min (cutting speed) and 4.0 mm (arc gap).The MRR value was 0.47 mm3/sec and Ra 4.52 µm. Error within 10 % was allowed.